Evaluation of human postural balance in quiet standing by direct measurement of human body center of mass acceleration - Kizilova, N.; Jarmalienė, E.; Šešok, A.; Daunoravičienė, K.; Griškevičius, J. (My University, 2009)
Present article deals with the evaluation of human postural balance in quiet standing by the direct measuring of center of mass acceleration. Displacements of subjects’ center of mass were determined and trajectories in anterior-posterior-medial-lateral plane were obtained. Comparison of parameters between subjects with stroke and healthy subjects was performed and measurements revealed higher sway amplitudes of subjects with stroke.
Keywords: Human postural balance; Center of mass acceleration; body sway; accelerometry